2022
DOI: 10.1002/mabi.202200208
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing GelMA/PVA Interpenetrating Polymer Networks Scaffolds Mediated with CuO Nanoparticles for Angiogenesis

Abstract: Biocompatible hydrogels have been considered one of the most well‐known and promising in various materials used in the fabrication of tissue‐engineering scaffolds. Although considerable progress has been made in recent decades, many limitations remain, such as poor mechanical and degradation properties of biomaterials. In addition, vascularization of tissue‐engineering scaffold is an enduring challenge, which limited the fabrication and application of scaffold with clinically relevant dimension. To cover these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Recent studies have reported that copper oxide nanoparticles (CuONPs) can also modulate ROS generation. Hu et al 66 found that GelMA/PVA IPN scaffolds modified with a group of copper oxide nanoparticles (CuONPs) also showed great potential in promoting angiogenesis during tissue growth and repair. In summary, inorganic components play a crucial role in bone regeneration by regulating mechanical properties and cell differentiation processes.…”
Section: Bioglass (Bg) Bg-xls/mentioning
confidence: 99%
“…Recent studies have reported that copper oxide nanoparticles (CuONPs) can also modulate ROS generation. Hu et al 66 found that GelMA/PVA IPN scaffolds modified with a group of copper oxide nanoparticles (CuONPs) also showed great potential in promoting angiogenesis during tissue growth and repair. In summary, inorganic components play a crucial role in bone regeneration by regulating mechanical properties and cell differentiation processes.…”
Section: Bioglass (Bg) Bg-xls/mentioning
confidence: 99%
“…119 Nevertheless, significant progress has already been made in this area recently. 60,61,[122][123][124] Lee et al demonstrated, as a proof of concept, the application of a human recombinant elastic bio-ink with which they could bioprint a vascularized cardiac construct that displayed the endothelium barrier function. 125 Therefore, constructing complex hierarchical vascularized networks in bioprinted tissue construct and establishing a connection with the host by surgical anastomosis or other technical solutions are issues that need to be addressed urgently.…”
Section: Clinical Translation Of Bioprinted Productsmentioning
confidence: 99%